Child Labour Sebagai Pelanggaran Jus Cogens Dalam Fast Fashion Industry Negara Cina - Nasrun, Andi Atthoriq (Brawijaya Law Student Journal, 2023)
Andi Atthoriq Nasrun, Hanif Nur Widhiyanti, Agung Ayu Nanda Saraswati Faculty of Law Universitas Brawijaya Jl. MT. Haryono No. 169 Malang e-mail: atthoriqnasrun@gmail.com   Abstract The fast fashion industry has experienced a concerning rise in child labor practices, particularly among multinational corporations operating in countries with lenient labor regulations. Children in fast fashion industries endure relentless exploitation, often forced into cramped, dimly lit factories where they work long hours under unsafe conditions, their small hands blistered and bodies fatigued, with no regard for their health, education, or basic rights. Although these practices are viewed as unethical by the international community, debates continue over whether child labor constitutes a violation of jus cogens norms under international law according to Lon Fuller’s theory. This research critically examines the classification of child labor in comparison with recognized jus cogens violations, such as slavery and human trafficking. Furthermore, this study aims to identify the parties responsible from an international law perspective. The research employs a normative methodology supported by statutory, conceptual, and comparative approaches. This study finds that child labor practices meet the criteria for jus cogens violations by fully satisfying Lon Fuller’s criteria, with responsibility attributed to the states that allow multinational corporations to operate and employ children. Keywords: Child labour, jus cogens, fast fashion industry, liability   Abstrak Industri fast fashion mengalami peningkatan praktik pekerja anak yang memprihatinkan, terutama di kalangan perusahaan multinasional yang beroperasi di negara-negara dengan regulasi ketenagakerjaan yang longgar. Anak-anak yang bekerja di industri tersebut mengalami eksploitasi, terkadang dipaksa untuk bekerja berjam-jam di pabrik yang sempit, gelap dan kondisi bekerja yang buruk. Kesehatan, edukasi dan hak dasar mereka juga tidak diperhatikan. Meskipun praktik ini dipandang tidak etis oleh komunitas internasional, perdebatan terus berlangsung terkait apakah pekerja anak termasuk dalam pelanggaran norma jus cogens dalam hukum internasional menurut teori Lon Fuller. Penelitian ini secara kritis mengkaji klasifikasi pekerja anak dibandingkan dengan pelanggaran jus cogens yang diakui, seperti perbudakan dan perdagangan manusia. Selain itu, penelitian ini bertujuan untuk menentukan pihak yang bertanggung jawab dalam kacamata hukum internasional. Penelitian ini menggunakan metodologi penelitian normatif yang didukung oleh pendekatan perundang-undangan, konseptual, dan komparatif. Di dalam penelitian ini, ditemukan bahwa praktik pekerja anak memenuhi sebagai pelanggaran jus cogens dengan secara sempurna memenuhi kriteria Lon Fuller dan yang pihak yang bertanggung jawab adalah negara yang mengizinkan perusahaan-perusahaan MNC untuk beroperasi dan mempekerjakan anak. Kata kunci: Child labour, jus cogens, fast fashion industry, tanggung jawab